Non-Union and Avascular Necrosis in Fracture Neck of Femur Fixed with Cannulated Screws in Young Adults (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To determine the frequency of non-union and avascular necrosis in fracture neck of femur in young adults fixed with cannulated screws.Methods: This descriptive Case series study of 55 patients was conducted from January 2012 to June 2014. Each case was followed up for a period of three months to observe non-union and avascular necrosis after neck of femur fracture. Fracture was stabilized in compression mode by cannulated screws.Results: There were 42 males and 13 females with male to female ratio 3.3:1. The mean age was 29.69Â±11.43 years. There were 47 patients having no avascular necrosis and 8 patients have avascular necrosis. Five patients have non-union and in 50 patients union achieved.Conclusion: we concluded in treating femoral neck fractures should include early diagnosis, early surgery, anatomic reduction, capsular decompression and stable internal fixation with cannulated screws.Key words: Non-union, Avascular Necrosis, Femoral neck fractures, Cannulated screw fixation.